El marketing relacional en la dirección de tránsito, movilidad y transporte del GADM Riobamba y su incidencia en la atención al cliente, 2017. - Villa Broncano, María José (2018)
The present research work leads to a descriptive analysis of the actual and current aspects of the Directorate of Traffic, Mobility and Transport of GADM Riobamba, therefore it is important to sustain theoretically with the review of several sources of bibliographical consultation and the study process, achieving effective results that are very useful aimed at a common good and development of the Directorate in Riobamba cantón, the purpose of the research is to assess the perception of relational marketing and its impact on customer service in the Directorate of Traffic, Mobility and Transportation of the GAD Municipal Riobamba, 2017. In the results obtained by the application of the survey it was possible to identify that both intemal clients and extemal customers have shortcomings that have to do with satisfaction, establishing that the level found in very satisfied is 13.91% something that is not encouraging for the Directorate , each one of the employees and workers being these human talent considered as the added valué, a relational marketing plan is proposed which will allow us to offer services adj usted to the needs and expectations of the clients with the creation of communication channels with the objective to guarantee lasting relationships with a climate of trust both internal and external